Brána do Dionýsova techno panství.: Autoetnografie estetiky rave kultury (mezi Berlínem a Prahou) - Orszulik, Eduard Adam (Lidé města, 2025)
This study examines the phenomenon of rave culture in its epicentre, Berlin, and confronts it with the Czech scene, which I have focused on as an insider in previous dance-anthropological research. In writing this study, I applied Jan Mukařovský’s aesthetic concept of function, norm, and value to the collected data. Mukařovský’s concept provides a relevant framework for exploring the role of aesthetics in the broader sociocultural context of rave culture, particularly in the context of forming communal identity, value sharing, and reflection on sociocultural influences. The purpose of this paper is to understand how aesthetics and the knowledge of subcultural symbols, codes, skills, values, and ideas, which can be described as subcultural capital, serve to preserve the ethos of rave culture and to maintain important values, including the creation of safe spaces. The rave scene in Berlin differs significantly from the Czech scene in many ways. First, it differs in terms of door policy, dimension, intensity, and state support. Clubs in Berlin are run as cultural institutions that have a major influence on shaping the local cultural and social space.